Proceso de atención de enfermería en adulto mayor con hiponatremia. - Romero Ramírez, Danna Alexandra (2023)
The present clinical case based on hyponatremia, in which the general objective was raised; apply the nursing care process in the elderly with hyponatremia. It is necessary to indicate that hyponatremia, which is defined as a sodium level below the normal range of 135 mMol/L, is the most common electrolyte imbalance both in clinical settings and in society. It can affect from 15% to 30% of hospitalized patients. The symptoms of hyponatremia are diverse and non-specific and are related to changes in the total water balance in the body, mainly affecting the cardiovascular and central nervous systems. Regarding the research methodology, it was based on a type of analytical study where a case study is analyzed. In reference to the results, that hyponatremia is based on an electrolyte disorder that is based on the decrease in sodium in the blood below its normal values, in addition, this disorder causes complications in the central and peripheral nervous system, and in the nervous system. circulatory. In conclusion, it was possible to apply the Nursing care process in the elderly with hyponatremia, in which care was applied by nursing professionals, based on the theory of Marjory Gordon and the taxonomies of NANDA, NIC and NOC., which made it possible to identify the altered patterns. The necessary requirements of the patient were covered in accordance with the altered patterns.